The institutionalized elderly: sociodemographic and clinical-functional profiles related to dizziness - Rosa,Tábada Samantha Marques (2016)
ABSTRACT INTRODUCTION: Dizziness is among the most common complaints in the elderly population. OBJECTIVE: To determine the sociodemographic and clinical-functional profiles of institutionalized elderly people related to dizziness. METHODS: Cross-sectional prospective study with institutionalized elderly people aged 60 or more years. A questionnaire on sociodemographic and clinical-functional characteristics was applied, and an anamnesis of occurrence of dizziness was held, as well as the Dizziness Handicap Inventory questionnaire. RESULTS: 48.9% of the elderly subjects had dizziness. The mean numbers of diseases and medications associated with dizziness were, respectively, 4.5 diseases and 7.8 medications. We found a significant association between the occurrence of dizziness and diseases of the musculoskeletal system, sub-connective tissue and genitourinary system, as well as the use of medications for the musculoskeletal system. The scores for handicap degree in functional DHI were significantly higher among elderly subjects who needed walking aids, who had suffered falls, and those manifesting anxiety. CONCLUSION: Our sample included subjects of advanced age, primarily women, who were institutionalized less than five years, with multiple diseases and polypharmacy users. They presented long-standing short-duration mixed dizziness, that occurred more than once a month and affected mainly the functional aspect.